Checklist of decapod crustaceans from the coast of the São Paulo state (Brazil) supported by integrative molecular and morphological data: III. Infraorder Brachyura Latreille, 1802 - Mantelatto, Fernando L.; Tamburus, Ana Francisca; Magalhães, Tatiana; Buranelli, Raquel C.; Terossi, Mariana; Negri, Mariana; Castilho, Antonio L. [UNESP]; Costa, Rogério C. [UNESP]; Zara, Fernando J. [UNESP] (Magnolia Press, 2020)
This checklist is the third part of a series derived from a long-term multidisciplinary project on the biodiversity of decapod crustaceans from marine and coastal environments of São Paulo state (Brazil). We integrated molecular techniques (DNA markers) and morphological analyses of adult specimens for accurate identifications. We compilated 185 species from the literature, but we confirmed the presence of 168 species: 130 of which we sampled, analyzed and obtained sequences (COI and/or 16S totalizing 113 sequences) and 38 that were not directly collected but were confirmed by analyses. In addition, 27 had their distribution removed from São Paulo due to uncertainties, and absence of material as voucher. Five species were reported for the first time on the coast of São Paulo (Calappa ocellata, Neohelice granulata, Teleophrys pococki, Teramnonotus monodi, Tetraxanthus rathbunae) and one on the Brazilian coast (Pseudomedaeus agassizi). Most of the non-sampled species previously reported on the coast of São Paulo might be considered doubtful records stablished in the past by inaccurate analyses, which assumed extended distribution to the area and/or misidentifications. At this time and based on our refined compilation, we can estimate the brachyuran diversity on the coast of São Paulo in 168 species. This detailed inventory contributes to the knowledge on the local decapod fauna by checking available dataset, adding new species records in São Paulo and new sequences to GenBank database. These data may serve as baseline for future identifications and studies on conservation, population genetics, biogeography and phylogenetics, which might flag species that deserve further investigations and concerns.
Keywords: 16S mtDNA; Biodiversity; COI; Crabs; Distribution